Pengaruh Disiplin Kerja Dan Pelatihan Terhadap Produktivitas Kerja Karyawan Pada PT. BPR Cipatujah Kantor Cabang Rancah - Gagan Chepy Septyana (Journal of Management and Creative Business, 2023)
This research aims to determine the effect of Work Discipline and Training on employee work productivity at PT. BPR Cipatujah KC. Scaffolding both simultaneously and partially. The population in this study were all employees of PT. BPR Cipatujah Rancah Branch Office with 34 people. The sampling technique used in this research was a saturated sampling technique, which means that the entire population was sampled in the research so that a sample size of 34 samples was obtained. This research uses a descriptive method with a quantitative approach. The type of data used is primary data. Test data quality using validity tests and reliability tests. The data analysis stage was carried out using quantitative analysis in order to analyze the collected data to prove the hypothesis. The research results show that work discipline has a positive and significant effect on employee work productivity at PT. BPR Cipatujah KC. Scaffolding is 44.00%. Partially testing the hypothesis obtained tcount > ttable (5.012 > 1.694) so ​​Ho is rejected and H1 is accepted, meaning that there is a positive and significant influence of work discipline on employee work productivity at PT. BPR Cipatujah KC. Scaffolding. Training has a positive and significant effect on employee work productivity at PT. BPR Cipatujah KC. Scaffolding is 28.40%. Partially testing the hypothesis obtained tcount > ttable (3.560 > 1.694), so Ho is rejected and H2 is accepted, meaning that there is a positive and significant influence of training on employee work productivity at PT. BPR Cipatujah KC. Scaffolding. Simultaneous hypothesis testing of work discipline and training has a positive and significant effect on work productivity with a coefficient of determination of 52.30% while the remaining 47.70% is influenced by other factors. Hypothesis testing obtained a value of Fcount > Ftable or (16.967 > 3.34), then Ho was rejected and H3 was accepted, thus there was a positive and significant influence of work discipline and work training on employee work productivity at PT. BPR Cipatujah KC. Scaffolding.